Neural crest cells and the evolution of a phenotypic syndrome - Pranter, Robin ; 0000-0003-3615-0281 (Biologiska institutionen, Lunds universitet, 2025)
The cell is the fundamental unit of life and in multicellular animals, all cells are derived from stem cells. To understand how stem cell development may influence phenotypic evolution, this thesis studies a population of vertebrate stem cells known as neural crest cells (NCCs). With unparalleled potency and migratory behavior, NCCs affect many different traits spread over the entire vertebrate body, for example fascial morphology, coloration and behavior. It has been posited that the fact that fact that NCC-derived traits share a developmental origin wire these traits together and thus facilitate the evolution of syndromes . This thesis studies the nigriventris syndrome that has evolved in the common wall lizard (Podarcis muralis) in Italy. Lizards with this syndrome show exaggerated expression of facial morphology (larger heads), coloration (extensive body melanization, bright green dorsal coloration, and enlarged UV-blue lateral spots) and behavior (aggressive and dominant behavior) relative to ancestral phenotypes . A variety of approaches are applied – from single-cell transcriptomics to staining of individual genes in whole embryos – to trace the origination, migration and differentiation of NCCs in embryos of the common wall lizard. Building on this, I developed a methodology to isolate NCCs using flow cytometry that does not require the use of transgenics or other manipulations. To test for differences in NCC biology associated with the nigriventris syndrome, I isolated NCCs from embryos of parents of nigriventris and ancestral origins and applied single-cell transcriptomics. I found that key aspects of NCC biology such as total number, proliferation, migration, and gene expression are all found to be increased in embryos from parents with the nigriventris phenotype. This hyperfunction of NCCs in nigriventris embryos supports the idea that NCC biology facilitates the evolution of phenotypic syndromes.
Keywords: Evolution; Developmental biology; evo-devo; Neural crest cells; Stem cell; Lizard; Developmental bias; scRNA-seq; Utvecklingsbiologi; neuralkammceller; stamceller; Ödla; developmental bias; stem cell; evo-devo; cell migration; cell differentiation; lizard; gene expression patterns; HNK-1; cell migratory routes; Squamata; reptile; fluorescence-activated cell sorting; non-model organism; cell type; transcriptional prfiles; single cell transcriptomics; RNA velocity; domestication syndrome; flow cytometry; scRNA-seq; cell cycle; devo-evo